Application of the rapid prototyping technique to design a customized temporomandibular joint used to treat temporomandibular ankylosis - Suresh M. Chaware; Vaibhav Bagaria; Abhay Kuthe (Indian Journal of Plastic Surgery)
Anthropometric variations in humans make it difficult to replace a temporomandibular joint (TMJ), successfully using a standard “one-size-fits-all” prosthesis. The case report presents a unique concept of total TMJ replacement with customized and modified TMJ prosthesis, which is cost-effective and provides the best fit for the patient. The process involved in designing and modifications over the existing prosthesis are also described. A 12-year- old female who presented for treatment of left unilateral TMJ ankylosis underwent the surgery for total TMJ replacement. A three-dimensional computed tomography (CT) scan suggested features of bony ankylosis of left TMJ. CT images were converted to a sterolithographic model using CAD software and a rapid prototyping machine. A process of rapid manufacturing was then used to manufacture the customized prosthesis. Postoperative recovery was uneventful, with an improvement in mouth opening of 3.5 cm and painless jaw movements. Three years postsurgery, the patient is pain-free, has a mouth opening of about 4.0 cm and enjoys a normal diet. The postoperative radiographs concur with the excellent clinical results. The use of CAD/CAM technique to design the custom-made prosthesis, using orthopaedically proven structural materials, significantly improves the predictability and success rates of TMJ replacement surgery.